Telegram - Schevenels, Walther, b. 1894
030-0069-001 = CT 300 300 F POST OFFICE OVERSEAS TELEGRAM Received at Central Telegraph Office Official particulars including Office of Origin. = 652 PARIS 23107 - 24 - 13 - 1720 = BELL TRADING SOWEST LONDON = AGREE 300 TONS OF FOOD TO BE SENT BARCELONA VIA BORDEAUX BARCELONA TO THE ADDRESS SANTIAGO ENRIQUE ARAGON 300 = SCHEVENELS Telegrams for all countries in the world and radio-telegrams for ships on all seas are accepted at all Postal Telegraph Offices or may be telephoned to the Post Office. For free repetition of doubtful words telephone NATIONAL 3383. If the telegram was received by telephone DIAL 559. This form and, if possible, the envelope should accompany any written enquiry. 292/946/30/69